The Criminal/Legal Experiences of Individuals with Mental Illness along the Sequential Intercept Model: An Eight-Site Study. (January 2021) - Comartin, Erin B.; Nelson, Victoria; Smith, Scott; Kubiak, Sheryl
Studies suggest that up to 44% of individuals in the criminal/legal system have a severe mental illness (SMI), and although diversion programs have been established, a significant portion still end up incarcerated. The Sequential Intercept Model is a framework designed to reduce the overrepresentation of individuals with SMI in the criminal/legal system by identifying points of interception to prevent individuals from entering or moving further into the system. Although studies assess programs in each intercept, none has evaluated how individuals process through all intercepts. Using data from eight counties ( N = 1, 160), this exploratory study assesses criminal/legal involvement across each intercept between individuals identified with ( n = 880) or without ( n = 280) SMI. Findings indicate longer stays in jail, low rates of treatment engagement and enrollment in specialty courts, and poorer diversion outcomes for individuals with SMI. Recommendations for research, policies, and practices are proposed to advance Smart Decarceration efforts.